Partitioning Dynamics of Nutrients in Transition Dairy Cows: Metabolic, Hormonal, and Cellular Mechanisms Affecting Lactation and Fertility - Md. Emran Hossain (International Journal of Nutritions, 2026)
This review critically examines nutrient partitioning dynamics in dairy cows during the transition phase, a period that profoundly affects lactation and reproductive performance. During this phase, cows experience extensive physiological changes that alter nutrient requirements and utilization, making effective management essential for health and productivity. The review synthesizes current research on mechanisms of nutrient partitioning, with particular attention to energy, protein, and mineral balance, which are crucial for optimizing milk yield, milk composition, and reproductive success. Proper nutrient management helps prevent negative energy balance, a common issue that can reduce milk production and impair reproductive efficiency. Metabolic disorders, including ketosis and milk fever, are discussed to highlight the importance of adequate nutrient provision in mitigating health risks. Environmental and management factors, such as housing, feeding strategies, and stress, are also examined, demonstrating the need for integrated approaches that address both nutrition and welfare. The review identifies gaps in existing knowledge, emphasizing opportunities for developing more precise feeding strategies and alternative feed resources to improve nutrient availability and utilization. Future research directions include the application of precision nutrition and the evaluation of novel feed ingredients to enhance transition-phase outcomes. By improving understanding of nutrient partitioning, dairy producers can implement strategies that support sustainable production, promote animal welfare, and increase economic efficiency. This comprehensive overview provides a foundation for advancing both scientific research and practical approaches in dairy cow nutrition and management, offering insights that are vital for optimizing performance during the critical transition period.
Keywords: Cellular signaling; endocrine regulation; fertility disorders; lactation performance; metabolic adaptation; nutrient partitioning; transition dairy cows